Inovasi Produk Es Lilin Nanas Sebagai Upaya Peningkatan Pendapatan Masyarakat Desa Kemang - Wahyuni, Ningsih; Sutikno, Hary; Prameswari, Femy Adelia; Marizka, Hany; Purnamasari, Endah Dewi; Anggraini, Leriza Desitama; Gumano, Hendry Natanael (Universitas Nusantara PGRI Kediri, 2024)
Kemang Village is one of the villages located in Lembak District, Muara Enim Regency, South Sumatra Province, which has great potential in the agricultural and plantation sectors, especially in pineapple cultivation. However, the potential of pineapple in Kemang Village is only sold as fruit to several regions, so the sales of processed products made from pineapples are still very limited. Therefore, an innovation in processing pineapples into a product is needed to enhance its market value. This community service activity aims to assist the community in processing pineapples, which are a potential resource of the village, into a higher-value product, as well as to create business opportunities and increase the income of the people in Kemang Village. This activity was conducted using socialization and training methods for making processed pineapple products, attended by the women and youth of Kemang Village. The result of this activity is the innovation of a processed pineapple product, namely pineapple ice pops, as well as the community of Kemang Village gaining new knowledge and skills in processing pineapples, which is the main potential in Kemang Village.